2019
DOI: 10.35940/ijeat.a1077.1291s419
|View full text |Cite
|
Sign up to set email alerts
|

5 Published By: Blue Eyes Intelligence Engineering and Sciences Publication (BEIESP) © Copyright: All rights reserved. Retrieval Number: A10771291S419/2019©BEIESP DOI:10.35940/ijeat.A1077.1291S419 Journal Website: www.ijeat.org Water Absorption Behavior on Natural/ Synthetic Fibre Reinforced Polymer Composites

Abstract: This paper deals with the effect of moisture absorption on single coconut sheath fiber and single glass fibre. Additionally, the moisture effect in fibre reinforced unsaturated polyester composites like coconut sheath (CS) and Glass mat (GM) composite. Initially, CS and GM fibre reinforced polyester composite were produced through hand layup followed by compression moulding method. CS/UPR and GM/UPR composites were made through water treatment by dipping those composites in ordinary water for various time inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It was discovered from the results that, 15 wt% snail shell-derived HAp-reinforced sample had the highest weight gain. Kalirasu et al (2019) 1 validated these results of weight gain and concluded that water aids in the transport of oxygen and ions. According to Agbeboh et al (2020), 8 the usage of polymer composites in bioengineering heavily depends on the dispersion of water in those materials.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It was discovered from the results that, 15 wt% snail shell-derived HAp-reinforced sample had the highest weight gain. Kalirasu et al (2019) 1 validated these results of weight gain and concluded that water aids in the transport of oxygen and ions. According to Agbeboh et al (2020), 8 the usage of polymer composites in bioengineering heavily depends on the dispersion of water in those materials.…”
Section: Resultsmentioning
confidence: 90%
“…The search for durable materials with a combination of distinct properties like good strength and fracture toughness as well as lightweight at a competitive cost has led to prime global interest in polymer-based composites. 1,2 Polymer-based composites consist of a polymer matrix and reinforcement(s) and are easy to process at low temperatures due to their flexibility. 3 They also possess high specific strength and modulus, fatigue resistance, and thermal stability properties that are desirable in most applications.…”
Section: Introductionmentioning
confidence: 99%